A Taoism-Based Intercultural Study of Lin Zhaohua's Directing Aesthetics - Zhao, Chengyun (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2026)
This thesis is a study of Taoism as evidenced in Lin Zhaohua's directing aesthetics from 1980 to 2025 in order to examine his contributions to the intercultural development of Chinese theatre in a globalised age. The central argument of this thesis is that Lin's search for a Taoism-like paradoxical balance between the styles/methods/aesthetics of indigenous Chinese performing arts and the that of foreign performance cultures enabled him and some of the contemporary Chinese theatre directors to challenge the restrictions of any theatrical traditions and express Chinese subjectivities in various threads of culture. Lin Zhaohua's attitudes towards cultural politics, directing aesthetics, and productions had a significant impact on the development of Chinese theatre and inspired not only some of his contemporaries but also some younger generations of theatre artists. By closely reading Lin's writings and (stage) productions, inspecting the secondary materials such as commentaries and interviews, and interviewing some scholars who are specialised in Lin Zhaohua studies or contemporary Chinese theatre studies, an overview of Lin's performances mirroring Lin's intercultural pursuits in the field of Chinese theatre under both political as well as globalising pressure after the proclamation of the Reform and Opening-Up policy will be demonstrated. Case studies of Lin's intercultural performances are classified into four thematic dimensions which respectively signify the cultural exchanges with regard to xiqu's acting aesthetics, dominant (socialist) realist huaju tradition, indigenous Chinese folk performing arts, and avant-garde theatre. Each of the four approaches warrants its own chapter. Chapter One focuses on Lin's absorption of xiqu's aesthetics, particularly in the 1980s, in which Lin's negative attitude towards copying xiqu's conventions and selective assimilation of its narrative acting are portrayed. Chapter Two covers productions that concern Lin's resolutions as well as methods of challenging the dominant (socialist) realist tradition of huaju since the 1980s. In Chapter Three, the traditional Chinese folk performing arts innovatively deployed in three of Lin's productions created during the 1990s are examined to explore how Lin pushed back against the decline of traditional Chinese performance cultures in a globalised performing market that was filled by foreign theatres, commercial theatres, and political theatres. Chapter Four takes mainly Lin's productions in the twenty-first century as examples to investigate how intercultural elements are achieved in his internationally received avant-garde productions. Although the titles of four chapters are described as "thematic dimensions", they predominantly focus on Lin's aesthetic achievements, because I wish to argue that Lin's achievements in the intercultural aesthetics reflect some thematic issues such as the crises faced the Chinese theatre artists in different aspects during different periods. In this research, analysis will touch upon two levels of the intercultural features in Lin's productions. The first level is a close examination of Lin's attitudes towards as well as methods of employing different performance cultures, which sees a standpoint of Chinese legacies and an open mind to foreign cultures. The second level is how Lin and some representatives of his contemporaries since 1980, facing the suppressions and challenges brought by socio-political and cultural factors, have pursued intercultural explorations in theatre-making. To evaluate and critique the intercultural features embodied in Lin's productions, Taoist ideas concerned with "the equal and connected relationship between different things" and "the Taoist paragon's achieving targets by doing nothing" will provide tools of assessment in this thesis. The Taoist epistemology of things can build a Chinese-based metaphysical ground for the interpretations of cultural exchange in Lin's productions. The interrogation of Lin's methods of experimenting with various performance cultures according to the life philosophy of Taoism yields a better understanding as to the intercultural development of Chinese theatre in the last forty-five years or so. More importantly, the analysis illustrates the theatre's opportunities to bring about a culturally integrated whole with the subjectivities of different cultures maintained.
APPROVED
Keywords: Taoism; intercultural performance; Lin Zhaohua; huaju; xiqu